By marvelous agreement. - De Jong, Dola 1911- (Knopf, 1960)
When a seventeen-year-old Dutch girl, who has grown up in a concentration camp and an orphanage, comes to the United States to live with a psychoanalyst and her teenage son and daughter, the three young people have trouble getting along until a summer at the ocean and their mother's impending remarriage force all three to face reality and maturity.